Diaphragm Walls Acting As Anchor Curtains Of Laterally Loaded Structures - Synopsis - J. Matos e Silva (Deep Foundations Institute, 1996)
The paper refers two examples of structures located in seismic areas (Cases 1 and 2). The first one (Case 1) is the Torroal Bridge, located about 100 Km South of Lisbon, in the road Troia-Grandola. The horizontal loads due to the seismic actions were mainly carried by an anchor curtain connected, to the abutments, by reinforced concrete struts-ties. For the some purpose diaphragm walls were also placed under the pile caps of the column foundations. The second one (Case 2) refers to a building located about 50 Km South of Lisbon, at Sesimbra, near a cliff. To reduce the horizontal displacements of the structure due to seismic actions, in order to prevent the endangering of the cliff stability, an anchor curtain was adopted and connected, to the structure, by prestressed anchors.